A formação do psicólogo para o atendimento a pessoas em situação de deficiência - Caetano, Nadja Carolina de Sousa Pinheiro (2009)
Disability condition was the theme of the current study which seeks a connection between Special Education and Psychology. The issue of this study came from the problem of how to evaluate, with frugality, complex courses on higher education, in order to verify how well they prepare future professionals to act with people on disability condition, based on what is recommended from the scientific knowledge body existent on this area and also inside the ethical behavior standards established to this profession. The objective of this study consisted in evaluating the impact of a psychology formation course in order to enable future professionals to provide assistance to people on disability condition. To substantiate the study, the concept of disability was initially used, so as to contextualize the acting of a psychologist with a certain public; considering the history, academic formation and acting of this professional with this specific population. Concluding the theoretical part, a synthesis of what literature brings as necessary abilities and competences to a psychologist is presented in order to provide an adequate treatment to the person on situation of disability at its multiple contexts. The methodological outline involved a correlacional study with two groups of students, one with 34 senior students (GEF) and another with 16 beginner students (GEI) from a psychology course at a Piauí higher education public institute. It also involved three instruments: ELASI (Likert Scale on Social Attitudes towards Inclusion), QPPD ( Disability Personal Perception Questionnaire ) and the QEAPPD ( Ethical Questionnaire on Psychological Treating to People on Disability Condition ). The study wishes to compare similarities and differences between the groups, concerning social attitudes towards inclusion, personal perceptions about deficiencies and expected and restricted ethical behaviour so as to identify the impact related to psychologists formation in order for them to act with people on disability condition. The results evinced that the senior students group showed more satisfactory answers than the beginners one, according to the instruments propound analysis, which were still unsatisfying, considering what is suggested by the literature and the profession s ethical code. The GEF group obtained better results than the GEI group at the QPPD , both groups obtained similar results at the ELASI and, at the QUEAPPD , the results varied according to the subjects from the ten evaluated dilemma-situations. The senior students showed better results than the beginners when the situation demanded technical knowledge, however the beginners showed better results when the situation was related to professional acting, because of their choice on not answering or not demonstrating a lack of knowledge, while the seniors chose to inform acting procedures, even though inadequate ones. The instruments used revealed themselves useful and inexpensive. It is important to emphasize that the present evaluation refers, exclusively, to the evaluation of one aspect of the investigated course, and that it is not extended to the course as a whole. The question of how to organize on a curriculum space and time enough to supply a better formation to the psychologist on acting with people on disability condition is, therefore, opened. It is suggested, for future studies, the reproduction of studies of this kind, as well as the creation and improvement of instruments which allow a cheap evaluation of the formation given from higher education courses to professionals who act with people on disability condition.